THE ROLE OF FOLK TRADITIONS IN FORMING LEGAL CULTURE OF STUDENTS OF LAW SCHOOLS - Ruzmetova , Novval (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The use of all the wealth of folk wisdom, which contains valuable ideas of training and education, plays an important role in the development of a modern personality. Folk traditions serve as a source for the development of humanistic culture of a person. The experience of the present shows that an inattentive attitude to the traditions of our people, to its past and present means the destruction of the connection between generations and causes irreparable damage to the moral formation of the individual. The era of change, which the people of Uzbekistan entered, led to great changes not only in the field of social policy, economy, culture, but also in the moral principles and guidelines of the individual, in its value orientations.